1986
DOI: 10.1128/jb.167.2.467-472.1986
|View full text |Cite
|
Sign up to set email alerts
|

RNA-DNA hybridization analysis of transcription of the plasmid ColV-K30 aerobactin gene cluster

Abstract: Plasmid pABN1 contains the genetic determinants for the aerobactin iron uptake system of plasmid ColV-K30. Transposon Tn1000 mutants of pABN1 defective in synthesis of a 50,000-dalton polypeptide were found neither to secrete nor to accumulate aerobactin, but were not impaired in iron transport functions, clearly indicating a role for this polypeptide in aerobactin biosynthesis. RNA-DNA hybridization studies with probes spanning the entire aerobactin gene cluster showed that the system is regulated at the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This calls into question the premise of correlating solely the ability to produce aerobactin with virulence. Although aerobactin-producing strains are found frequently in faeces (Table 3), whether or not aerobactin contributes to the virulence of enteropathogenic Escheriehia cell is still a controversial issue (50,90,91). Statistical data will probably always be somewhat inconclusive until (a) a reliable experimental model is devised in which aerobactin production is the only variable and (b) the ability of nonproducing strains to use aerobactin as an iron source is more thoroughly investigated.…”
Section: The Highest Percentage Of Aerobactin-producingmentioning
confidence: 97%
See 1 more Smart Citation
“…This calls into question the premise of correlating solely the ability to produce aerobactin with virulence. Although aerobactin-producing strains are found frequently in faeces (Table 3), whether or not aerobactin contributes to the virulence of enteropathogenic Escheriehia cell is still a controversial issue (50,90,91). Statistical data will probably always be somewhat inconclusive until (a) a reliable experimental model is devised in which aerobactin production is the only variable and (b) the ability of nonproducing strains to use aerobactin as an iron source is more thoroughly investigated.…”
Section: The Highest Percentage Of Aerobactin-producingmentioning
confidence: 97%
“…The genetic and functional organization of the aerobactin determinants encoded by Escherichia coli plasmids pColV-K30 (49,(50)(51)(52)(53) and pColV-K311 (54, 55) have been completely ascertained and found to be virtually identical to each other. This acrobattin system spans about 8 kilobases of DNA and consists of a cluster of five genes (iucABCD, iutA) arrayed in an operon (9).…”
Section: Enterobacfin and Aerobactinmentioning
confidence: 99%
“…However, overwhelming evidence from different laboratories later demonstrated that the peptide was instead involved in aerobactin biosynthesis (11,44), in particular in the step of NM-hydroxylation of L-lysine (16,24) which precedes the eventual synthesis of the aerobactin molecule.This assignment, based on complementation analysis (23) and studies on accumulation of aerobactin precursors by different mutants (16,24), is consistent with recent in vitro studies made with the unpurified protein (27). In addition, Coy et al (13) showed that N6-hydroxylysine is the substrate for the purified acetylase, the enzyme which mediates the next step in the biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which such exchange could occur, however, is not known. Previously it has been proposed that iron supplied to iron-stressed bacteria by aerobactin, unlike that delivered by enterochelin, exists in an intracellular complexed form rather than being released into a cytoplasmic pool, since cells using aerobactin for growth were insensitive to the iron-dependent anti biotic streptonigrin (Williams & Carbonetti, 1986). One possibility suggested by the data presented here is that aerobactin may have a role in intracellular storage and mobilization of ferric iron within the cytoplasm.…”
Section: Discussionmentioning
confidence: 60%
“…It should be stressed, however, that these plasmids are not directly comparable. First, the aerobactin operon in plasmids pABNI and ColV-K30 is iron regulated (Roberts et al 1986). Second, ColV-K30 has a copy number of one or two per cell, while pLG141 and pABN I are multicopy plasmids.…”
Section: Eflect Of Endogenous Siderophores On Aerobactinmentioning
confidence: 99%